2006
DOI: 10.1099/vir.0.81628-0
|View full text |Cite
|
Sign up to set email alerts
|

Raf/MEK/ERK signalling triggers reactivation of Kaposi's sarcoma-associated herpesvirus latency

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) causes Kaposi's sarcoma, primary effusion lymphoma and multicentric Castleman's disease. KSHV infection of cells produces both latent and lytic cycles of infection. In vivo, the virus is found predominantly in the latent state. In vitro, a lytic infection can be induced in KSHV-infected cells by treating with phorbol ester (TPA). However, the exact signalling events that lead to the reactivation of KSHV lytic infection are still elusive. Here, a role is demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 31 publications
4
48
0
Order By: Relevance
“…6C). As shown previously by Cohen et al (7) and Ford et al (10), TPA treatment led to a 7.8-fold increase in phospho-ERK levels. These results demonstrated that irrespective of the upstream pathway mediating ERK phosphorylation, this activation is essential for lytic cycle induction by both TPA and neomycin.…”
Section: Increasedsupporting
confidence: 65%
“…6C). As shown previously by Cohen et al (7) and Ford et al (10), TPA treatment led to a 7.8-fold increase in phospho-ERK levels. These results demonstrated that irrespective of the upstream pathway mediating ERK phosphorylation, this activation is essential for lytic cycle induction by both TPA and neomycin.…”
Section: Increasedsupporting
confidence: 65%
“…Besides JAK/STAT signaling, huIL-6 also involves activation of mitogen-activated protein kinase and phosphatidylinositol-3-kinase/AKT pathways. More recent studies have indicated that Raf/MEK/ERK signaling modulates TPA-induced reactivation of KSHV latency (20,25); therefore, our results did not eliminate the possibility that another pathway(s) by huIL-6 may also be involved in this process.…”
Section: Discussionmentioning
confidence: 49%
“…We next tested to see whether latent ZEBOV infection, like other latent infections, such as herpesvirus or human immunodeficiency virus (HIV) (30)(31)(32), could be induced to replicate to higher titers through physiological treatments. Typically, RAW ZEBOVpi cells produced low levels of viral expression, as determined by GFP expression (Fig.…”
Section: Resultsmentioning
confidence: 99%